In vivo analgesic, anti-inflammatory potential in Swiss albino mice and in vitro thrombolytic activity of hydroalcoholic fruits extract from Daemonorops robusta Warb - Mir Muhammad Nasir Uddin, Shahriar Ahmed, Mohammad Shah Hafez Kabir, Mohammad Sofiqur Rahman, Ramiz Ahmed Sultan,Talha Bin Emran (Journal of Applied Pharmaceutical Science, 2017)
Objectives: The analgesic, anti-inflammatory and thrombolytic potential of Daemonorops robusta Warb, a Bangladeshi tribal medicinal plant was studied for the first time. So our aim was to evaluate analgesic, anti-inflammatory and thrombolytic activities of fruit extract of D. robusta. Methods: Fresh fruits of plant were extracted with methanol and then subjected to preliminary phytochemical screening. Analgesic activity of the extract was performed against acetic acid induced writhing, hot plate and formalin induced test. Anti-inflammatory effect was evaluated using carrageenan induced paw edema in mice. An In Vitro thrombolytic model was used to check the clot lysis potential of the extract. Results: Phytochemical screening showed the presence of alkaloid, carbohydrate, flavonoids, steroid, phlobatanin and saponin. The extract exhibited significant analgesic effect (P
Keywords: Daemonorops robusta,Analgesic activity,Anti-inflammatory activity,Thrombolytic activity.